Ventajas de los biopreparados para controlar enfermedades, como alternativa de la agricultura orgánica - Muñoz Díaz, Anddy Jacinto (2020)
This document, as a practical component of a Complex nature, was developed in order to determine the advantages of biopreparations to control diseases, as an alternative to organic agriculture. The use of biopreparations leads to a sustainable agriculture that allows improving and preserving human health, through the use of inputs or pesticides of animal and vegetable origin, that do not cause environmental pollution and that optimize the quality of the crops. The conclusions raised determined that it is necessary to make producers aware of the importance of implementing a sustainable organic production, through the use of biopreparations for disease control, demonstrating their economic and environmental results, because when applying them there is less risk of contamination since they are manufactured with biodegradable or low toxicity substances; The plant and animal resources available must be used for the elaboration of biopreparations, becoming an alternative at low cost and their use to conserve soils, prevent and control diseases; the symptoms of diseases caused by fungi diminish with the application of biopreparations, due to their action and rapid degradation, which makes it less aggressive against beneficial organisms and develops slower resistance, unlike synthetic products.